opaque-2 modifiers increase gamma-zein synthesis and alter its spatial distribution in maize endosperm. - Geetha, K B (1991)
Through the action of opaque-2 modifier genes, the soft, floury endosperm of opaque-2 mutants is converted to a vitreous phenotype. This change in endosperm texture is associated with a twofold to threefold increase in gamma-zein content. To investigate the effect of opaque-2 modifiers on the expression of gamma-zein genes, we analyzed the synthesis and distribution of gamma-zein protein and the level of gamma-zein mRNAs in developing endosperms of the inbreds W64A and W64Ao2, a modified opaque-2 mutant Pool 34 QPM, and their reciprocal F1 hybrids. We also characterized the number and organization of gamma-zein genes in these and related maize genotypes. Our studies show that opaque-2 modifiers are semidominant genes, resulting in a twofold to threefold increase in gamma-zein gene expression in both opaque-2 and normal genetic backgrounds. The increase in gene expression appears to be a consequence of enhanced mRNA transcription or stability rather than gene amplification because gamma-zein genes occur in one or two copies in modified as well as nonmodified genetic backgrounds. Ultrastructural studies showed that gamma-zein occurs in high concentrations in the first few subaleurone cells of nonmodified endosperms, but high concentrations of gamma-zein occur in the subaleurone and central endosperm cells of modified opaque-2 mutants. The increased concentration and distribution of gamma-zein in modified endosperms are highly correlated with the activity of opaque-2 modifier genes.